?NITROGEN REQUIREMENTS FOR TWO PROMISING LINES OF WHEAT UNDER RAINFED CONDITIONS (Biological Sciences - PJSIR, 1996)
A studywas conductedon aloam soilto'indentify optimum nitrogenrequirementsfor two promising lines (8706 and 89 R-35) of wheat (Triticum aestivum L.) during 1992-93under rainfed conditions at Barani Agricultural Col- lege Farm, Rawalpindi. There were four N fertilizer application rates viz. 100, 125, 150 and 175 kg ha'. Nitrogen application rates @ 150and 175kg ha' produced equally significant tall plants with good ear length. No significant differences weremeasured for harvest index and 1000 grain weight. Number of heads rrr? and number of grains spike-Idemonstrated increasing trend to varying N rates. Plots fertilized with N @175kg ha' produced higher yields of grain and straw (3070 and 5314 kg ha', respectively) in comparison to rest of the N rate treatments. The interac- tions between N-rates and varieties were non-significant with the exception of head numbers m? and grain weight spike". TIleline 8706 was superior to the line 89R-35 in respect of grains whereas the line 89R-35 performed better for straw yield. The line 89R-35 was found to be more economical and profitable than the line 8706 and afforded highest cost benefit ratio of 3.8..